COVID-19 in newborns and in children: the state of the art - Paraluppi, Valentina; Pintus, Maria Cristina; Fanos, Vassilios; Marcialis, Maria Antonietta (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2020)
Novel COronaVIrus Disease 2019 (COVID-19) is an emerging disease of public health concern because it is caused by a newly identified pathogen, against which humans have no pre-existing immunity. Since its outbreak, a growing number of studies have examined COVID-19 in adults, but the data on its epidemiological and clinical characteristics in newborns and in children are few and patchy. Children appear to develop moderate-mild or silent forms of the disease; to our knowledge, only two cases of death (a 14-year-old and a 16-year-old teenagers) have been reported. Arguably, the number of pediatric cases may be underestimated, since presumably cases with mild or no symptoms are not brought to the doctor’s attention. We have selected the most interesting and significant papers (including some pre-publication or ahead-of-print papers). The key factors in the pathophysiology of COVID-19, available data on pregnancy, the neonatal period, and later are discussed. A review of pediatric cases is available and 3 practical algorithms help the reader in clinical choices. Finally, diagnostic criteria and treatment are presented.